Analysis of Human Resources Training and Development Strategy on The CV. Cakrawala - Leonora Puspa (ProBisnis : Jurnal Manajemen, 2023)
The purpose of the research is to explain the analysis of needs, methods, benefits, supporting factors, inhibiting factors and training evaluation methods and human resource development strategies on CV. Cakrawala. This research is a qualitative approach. The method of data collection used is observation, semi-structured interviews, and documentation. The results of this study explain the strategy of training activities and human resource development on CV Cakrawala which is run based on the analysis of the work requirements of employees. The method used is the method in the classroom and the method of training in work. Training and development strategies are believed to be beneficial for employees and companies in an effort to increase competency so that the final results can be assessed, namely the results of their work. Basically a company engaged as a goods distributor fully supports the existence of training and strategic development activities. The attention of top management and employee motivation is less a limiting factor in attending training. Evaluation of activities is carried out through sharing sessions between employees and top management.